Paciente femenino de 8 años con asma bronquial. - Escobar Jimenez, Allison Nicolt (2022)
Bronchial asthma is a chronic respiratory disease that affects human beings of all ages throughout the world. Its origin is uncertain, determined by predisposing and triggering factors that result from a specific phenotype. This study presents the case of an 8-year-old schoolgirl with a family pathological history (FPA) of bronchial asthma, who comes accompanied by her parents to the Vinces Public Health Center in the emergency area, with symptoms clinical “acute bronchial asthma” presenting symptoms (fever, fatigue, persistent dry cough and wheezing chest noises). The patient is admitted with pharmacological treatments and medical observation for 24 hours of evolution.